Dynamik von Staubteilchen in Saturns E-Ring - Beckmann, Uwe (2008)
This thesis covers the dynamical evolution of dust in the outer Saturnian magnetosphere, the region of the large E ring. For the dynamical evolution a model is used, which considers the gravitation of Saturn, including the quadrupolmomentum due to Saturn’s oblateness, the gravi- tation of Saturn’s large moons embedded in the E ring, the influence of the surrounding plasma as charging of the grains and sputtering, the Lorenz force due to Saturn’s rotating magnetic field, and the radiation pressure caused by the sun. In this model, the charge of the grain is characterised by time depended charge currents. The material parameters are derived from the comparison with measurements of the grain potential by the dust analyser onboard the spacecraft Cassini. Further measurements done by various scientific instruments of Cassini discover a geologic active south pole on the icy moon Enceladus. This dust plumes are determined as the main source of fresh E ring particle...